Divergent Outcomes of Carbene Transfer Reactions from Dirhodium- and Copper-Based Catalysts Separately or in Combination - Xu, Xinfang (2011)
The use of copper and rhodium catalysts separately and in combination directs reactions between vinyldiazoacetates 3 and cinnamaldehydes 2 to from formal [4+3]-cycloaddition (epoxidation followed by Cope rearrangement), intramolecular cyclopropanation, and Mukaiyama-aldol reactions selectively and in high yield.